2022
DOI: 10.3390/nano12111833
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Strengthening Effect of Graphene-Nanoplates in Al Matrix Composites by Heterogeneous Matrix Design

Abstract: In the present work, the properties of graphene-nanoplates/aluminum (GNPs/Al) composites with a heterogeneous matrix design were investigated. The advantage of the heterogeneous matrix was investigated by the finite element method. Then, 0.6 wt.% (GNPs/6061Al)/2024Al (heterogeneous matrix) and 0.6 wt.% GNPs/6061Al composites were prepared by ball milling, pressure infiltration technology, and hot extrusion. The aggregation of GNPs was eliminated and the interlayer slide of GNPs was observed. Mechanical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…However, no peaks of GNPs are observed because of the low graphene content and the limited resolution of elements of X-ray diffraction. Research studies by Shao et al [ 29 ] and Lou et al [ 30 ] have also reported these findings on the absence of GNPs. In addition, there was no obvious peak of the aluminium carbide (Al 4 C 3 ) phase found, thus proving that there was no chemical interaction between GNPs and Al alloy.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…However, no peaks of GNPs are observed because of the low graphene content and the limited resolution of elements of X-ray diffraction. Research studies by Shao et al [ 29 ] and Lou et al [ 30 ] have also reported these findings on the absence of GNPs. In addition, there was no obvious peak of the aluminium carbide (Al 4 C 3 ) phase found, thus proving that there was no chemical interaction between GNPs and Al alloy.…”
Section: Resultsmentioning
confidence: 53%
“…On the other hand, Figure 7 d,f indicate a high accumulation of carbon (C) in the red strip-like phase as GNPs. Agglomeration of GNPs at several locations is observed for 0.5 wt.% and 1.0 wt.% of GNPs/Al composites as a result of a high percentage of GNPs, where the liquid metal has segregated the graphene particles and impeded them from mixing with the aluminium matrix [ 24 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Solid-phase mixing is usually carried out through the powder processing method that is usually proceeded via ball milling or shear mixing. 147,148 Before solution mixing, surface modification of the inorganic material NPs and/or GD sheets is often carried out, so that they can bind through either the covalent interactions (chemical bonding) or the non-covalent interactions (van der Waals forces, hydrogen bonding, π-π stacking, or electrostatic interactions). 20,146 As an example of inorganic NPs/GD covalent interactions, Liu et al 149 demonstrated efficient immunosensor for detection of cardiac marker troponin-I, based on GO/Au NPs nanocomposite that was prepared by solution mixing.…”
Section: D Graphene Derivatives/inorganic Materials Compositesmentioning
confidence: 99%
“…The primary fabrication processes, also called densification techniques, of the inorganic material NPs/2D GDs composites include, hot extrusion, hot pressing, cold pressing and sinter molding. 19,147,148 Up to date, various sinter molding methods have been employed, including pressureless sintering, field-assisted sintering, high-frequency induction heated sintering, microwave sintering, spark plasma sintering and flash sintering. 148 Recent distinctive characteristic properties 2D Graphene derivatives/metals composites.…”
Section: D Graphene Derivatives/inorganic Materials Compositesmentioning
confidence: 99%
See 1 more Smart Citation